DEVELOPING COUNTER-HEGEMONIC PEDAGOGY IN ADULT & HIGHER EDUCATION - Mervin Chisholm (Adult Education Research Conference, 2015)
Using various discourses including critical theory, critical pedagogy, postmodernism, feminist pedagogy and liberation theology, the importance of counterhegemonic pedagogy is underscored. This approach to pedagogy can be facilitated through various methodological engagements but the discussion is about reasoning and counter-storytelling.
Keywords: counterhegemonic; pedagogy; reasoning; counter-storytelling